2017
DOI: 10.5334/ijic.2574
|View full text |Cite
|
Sign up to set email alerts
|

“Go Make Your Face Known”: Collaborative Working through the Lens of Personal Relationships

Abstract: Background:Collaborative working between professionals is a key component of integrated care. The academic literature on it largely focuses either on integration between health and social care or on the dynamics of power and identity between doctors and nurses. With the proliferation and extension of nursing roles, there is a need to examine collaborative working amongst different types of nurses.Method:This study explored experiences of collaborative working amongst generalist and specialist nurses, in commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
0
9
1
Order By: Relevance
“…We did not find a significant impact for trust and familiarity on conversation structures, whereas other (mostly qualitative) studies reported that mutual trust and positive interpersonal relations are essential for better collaboration and communication between nurses and physicians [1,3,6,20]. A lack of power and validity of the instruments to measure trust and familiarity in the present study may explain our inability to find similar associations.…”
Section: Relation To Existing Literaturecontrasting
confidence: 99%
See 1 more Smart Citation
“…We did not find a significant impact for trust and familiarity on conversation structures, whereas other (mostly qualitative) studies reported that mutual trust and positive interpersonal relations are essential for better collaboration and communication between nurses and physicians [1,3,6,20]. A lack of power and validity of the instruments to measure trust and familiarity in the present study may explain our inability to find similar associations.…”
Section: Relation To Existing Literaturecontrasting
confidence: 99%
“…Ineffective patient-related communication between professionals is common in primary healthcare and negatively impacts the quality of care provided [1]. The number of community-dwelling elderly and chronically ill patients with complex multiprofessional care needs is growing [2], meaning that effective interprofessional collaboration and communication in primary care is becoming increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…In the terminology of Boon et al [28] these interactions were usually consultative in nature, but sometimes they also involved mutual exchange of information and discussions of treatment options. A recent study among nurses in community and acute settings also found that the professionals appreciated the relational advantages of face-to-face communication offered by co-location [29]. However, in our cases cross-sectoral interactions were mostly sporadic, and most professional work was carried out separately in the two sectors within the health centres.…”
Section: Discussionmentioning
confidence: 53%
“…The limited realist stance underpinning this study is in keeping with our concern with subjective personal accounts from mental health nurses working in applied healthcare settings. This approach has been successfully used previously in healthcare research, including research with healthcare professionals (King, Bravington, Brooks, Melvin, & Wilde, ; Waddington & Fletcher, ). An inductive, data‐driven approach to analysis was appropriate for this study as our aim was to explore and understand the mental health nurse perspective.…”
Section: Methodsmentioning
confidence: 99%